Cyber communion: finding God in the little box - Ostrowski, Ally (The journal of religion & society, 2006)
In the age of the internet people are finding new ways to connect with each other and also new ways to connect with the divine. This study explores the relationships between people in an online religious worship service at the UK-based Church of Fools and assesses whether the virtual bonds of community are strong enough to provide spiritual fulfillment. The project also investigates offering Holy Communion in a virtual church environment to assess why some worshippers would be satisfied with an online representation of the Eucharist and others would still look to physical churches for the ritual of Holy Communion. The results suggest a link between those who visited the church more often, developed a stronger bond with others worshippers, and subsequently received a higher level of spiritual fulfillment from the online service, including being more receptive to receiving virtual communion.